Guru Penggerak: A Literature Review from the Perspective of Anthony Giddens' Structuration Theory - Ahmad Jum’a Khatib Nur Ali; Yasir Riady; Muhammad Ajmal; Lina Gurung (Indonesian Journal of Pedagogy and Teacher Education, 2025)
The Guru Penggerak is a leadership program designed to train teachers in leadership so that they can become learning leaders. Therefore, the Guru Penggerak program needs to be examined conceptually to enrich the program's insight dimensions. This study is conceptual research, which explores the conceptual relationship between Guru Penggerak (Mobilizing Teachers) and the practice of organizational culture in schools. This research aims to explore the conceptual connection between Guru Penggerak and leadership within organizational culture from the perspective of social change. This research employs library research with a descriptive method to elaborate on the concepts discussed in the study. Anthony Giddens’ Structuration Theory is the analytical tool to conceptually understand Guru Penggerak as a social agency. The research highlights Guru Penggerak as a social agent capable of influencing and shaping school culture. The findings suggest that the leadership practices embodied in the Guru Penggerak program can contribute meaningfully to the development and transformation of organizational culture within educational institutions. Thus, a deeper conceptual understanding of this relationship can enrich the program's framework and support its implementation in fostering sustainable change in schools.